2020
DOI: 10.1038/s41467-020-17883-1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the fundamental fibrotic processes driving abdominal adhesion formation

Abstract: Adhesions are fibrotic scars that form between abdominal organs following surgery or infection, and may cause bowel obstruction, chronic pain, or infertility. Our understanding of adhesion biology is limited, which explains the paucity of anti-adhesion treatments. Here we present a systematic analysis of mouse and human adhesion tissues. First, we show that adhesions derive primarily from the visceral peritoneum, consistent with our clinical experience that adhesions form primarily following laparotomy rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…Human gene PDGFRA encodes platelet-derived growth factor receptor α, both a deficit and excess of which worsen reproductive potential through skeletal defects in newborns [ 75 ] and predisposition to infertility after infections [ 76 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human gene PDGFRA encodes platelet-derived growth factor receptor α, both a deficit and excess of which worsen reproductive potential through skeletal defects in newborns [ 75 ] and predisposition to infertility after infections [ 76 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanically, MSLN + MCs is the important subpopulation of MCs involved in the development of adhesion. Foster et al 41 recently found that JUN expression was strongly induced and correlated with prominent MSLN expression, and inhibition of JUN significantly minimizes adhesion formation.…”
Section: Cellular Mechanisms Of Pamentioning
confidence: 99%
“…Of importance, Foster et al analysed adhesions from patients and mouse models to elucidate the heterogeneity and source of fibrogenic cells. Fibroblasts within adhesions were found to express platelet derived growth factor receptor alpha (PDGFRA), a transmembrane receptor tyrosine kinase, as well as fibroblast markers, such as αSMA, vimentin, and collagen 1 (COL1) [ 92 ]. In murine ischaemic tissue-induced adhesions, fibroblasts expressed JUN (proto-oncogene, named after viral homolog v-jun in avian sarcoma virus 17), which is a transcriptional master regulator of fibrogenesis, and a portion of these cells were also positive for the mesothelial marker mesothelin (MSLN).…”
Section: Serosal Repair and Adhesion Formationmentioning
confidence: 99%
“…Analysis of these clusters in relation to their timepoints revealed that early JUN activation promoted a profibrotic state as reflected in the expression profiles. Moreover, inhibition of the highly expressed Jun/Jak/Stat pathway was found to reduce adhesion formation and was proposed as a novel preventative strategy [ 92 ].…”
Section: Serosal Repair and Adhesion Formationmentioning
confidence: 99%
See 1 more Smart Citation